Rozważania Jana Pawła II o istocie nauki społecznej Kościoła - Piątkowski, Wiesław (Annales. Etyka w Życiu Gospodarczym, 2012)
The source basis of the article is composed of pope John Paul’s II encyclicals – Laborem exercens (1981), Solicitudo rei socialis (1987), Centesimus annus (1991), Fides et ratio (1998), the Apostle’s Letter Tertio Millennio adveniente (1994) as well as the interview with priest cardinal Karol Wojtyla given to Vittorio Possenti on 21st of June 1978 in Mediolan. I shall separate the following issues:1) relations of concepts: social teaching of the Church, social doctrine of the Church and catholic social teaching; 2) relation theory – practice from the point of view of social doctrine of the Church; 3) social doctrine of the Church versus ideology; 4) in what sense may we talk about the historism of social doctrine of the Church?; 5) periodisation of the development of social doctrine of the Church.